BAHASA INDONESIA SEBAGAI PENGANTAR DALAM DUNIA PENDIDIKAN DI MI HIJRATUL FATH CIMAHI UTARA - Neni Nur'aeni; Mia Kusnur'aeni; Agus Priyanto (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the influence of Indonesian in the world of education in delivering the process of learning foreign languages and regional languages. This study aims to examine the use of Indonesian Language in a study at the Madrasah Ibtidaiyah Hijratul Fath Cimahi Utara. The problems in this study are: 1) What is the role of Indonesian in the world of education? 2) Can using Indonesian language help the learning process in delivering foreign language learning and regional languages? 3) How to use good and correct Indonesian Language so that it can help the learning process? The purpose of this study is to determine the extent of the influence of Indonesian in the world of education so that it is very influential in other subjects. The research method used is qualitative research methods. The research instrument used by researchers was interviews. The research object was three teachers and the research location at the Madrasah Ibtidaiyah Hijratul Fath school in North Cimahi. The results of the study show that the dominant Indonesian language is used in speech events, because the language of instruction in learning uses Indonesian. Thus, the role in the world of education is very influential in the world of education that we should apply as an introduction in applying learning English and Sundanese.